Unexpected synthesis of a novel heterocyclic system – (7E, 10aE)-2, 7-Dimethylfuro[3′, 4′:6, 7]cycloocta[1, 2, 3-cd]indole-8, 10(2H, 6H)-dione. Issue 27 (5th July 2017) - Rybalkin, Vladimir P.; Borodkin, Gennadii S.; Tkachev, Valerii V.; Yu. Zmeeva, Sofiya; Popova, Lidiya L.; Dubonosov, Alexander D.; Bren, Vladimir A.; Aldoshin, Sergey M.; Minkin, Vladimir I.
Graphical abstract: Highlights: Novel furocycloocta[ c, d ]indole heterocyclic system was synthesized. The Stobbe condensation was used on the first two stages. The structure was confirmed by 1 H, 13 C NMR and single crystal X-ray diffraction. Abstract: The first derivative of a novel heterocyclic system, (7 E, 10a E )-2, 7-dimethylfuro[3′, 4′:6, 7]-cycloocta[1, 2, 3- cd ]indole-8, 10(2 H, 6 H )-dione, was synthesized based on the Stobbe condensation of 3-chloro-1-methylindole-2-carbaldehyde with diethyl isopropylidenesuccinate. Cyclization of the 2-indolyl-containing diacid, formed by subsequent hydrolysis of the condensation product, did not lead to the expected fulgide, but rather to an unprecedented tetracyclic compound, the structure of which was established by 1 H, 13 C NMR, IR spectroscopy, mass-spectrometry and single crystal X-ray diffraction.